“Pasang”, Knowledge and Implementation of Local Wisdom in The Kajang Traditional Forest Area, South Sulawesi - Nurmala nurmala; Muh Dassir; Supratman supratman (Politeknik Pariwisata Makassar, 2022)
The Kajang tribe as a cultural and environmental tourism destination is a community of indigenous people who live in harmony with nature by having the life principle of